Crohn’s Ulcerative Colitis. Colectomy. Ileostomy. Ilecsigmoidostomy.: Evolutive Evaluation - Gutiérrez Galiana, Horacio; Falconi, Luis; Gutiérrez Blanco, Horacio; Praderi, Luis (Cirugía del Uruguay, 1981)
Report of an exceptional case of segmentary Crohn's Colitis, in left angie and its branches; fistula of sigmoid at psoas, simulating coxofemoral arthritis.